Delia, Jackson County - Horner, Kelsi (Kansas State University, The Chapman Center for Rural Studies, 2011)
Delia, even though it may be labeled a “lost town,” is fighting the label, battling to bring their town back to life. The history of Delia runs deep. Building upon on the determination instilled by their forefather, who prevailed in the debate over the town’s location, citizens of the little town might gather strength and win the battle.
Kelsi Horner, “Delia, Jackson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/56.
Keywords: Cross Creek; David W. and Delia Cunningham; Jackson County; Pacific Railroad; District #54; Washington Township High School